Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $G$ be a group, and $a$, $b \in G$

  • $(bab^{-1})^{n} = ba^{n}b^{-1}$, for every positive integer $n$ \begin{align*} \text{Let P(n) be the statement: } (bab^{-1})^{n} &= ba^{n}b^{-1} \newline \text{Show the base case P(1) : } bab^{-1} &= bab^{-1} \newline \text{Assume P(k) is true : } (bab^{-1})^{k} &= ba^{k}b^{-1} \newline \text{Now I need to show P(k+1) is true by multiplying P(k) by } bab^{-1} \newline (bab^{-1})^{k}(bab^{-1}) &= ba^{k}b^{-1}(bab^{-1}) \newline &= ba^{k}(b^{-1}b)ab^{-1} \newline &= ba^{k}ab^{-1} \newline &= ba^{k+1}b^{-1} \newline \text{Which is the statement P(k+1)} \end{align*}

  • If $a^{-1}$ has a cube root, so does $a$.

If $a^{-1}$ does have a cube root, then there is an element $x$ in $G$ such that $a^{-1} = x^{3}$. \begin{align*} a^{-1} &= x^{3} \newline a^{-1}a &= x^{3}a \newline e &= x^{3}a \newline (x^{-1})^{3} &= (x^{-1})^{3}x^{3}a \newline (x^{-1})^{3} &= a \end{align*}

Comments on the correctness or ways to improve either proof would be appreciated :)

share|improve this question
2  
As far as I can tell, those both look fine. –  yunone Jul 28 '11 at 2:26
2  
@Jon: They are all fine; but you can do the second one simpler by just taking inverses on both sides: if $a^{-1}=x^3$, then $a = (a^{-1})^{-1} = (x^3)^{-1} = (x^{-1})^3$. –  Arturo Magidin Jul 28 '11 at 2:33
add comment

2 Answers

up vote 0 down vote accepted

Both of the proofs look good to me.

share|improve this answer
add comment

HINT $\ \ \ $ Both answers follow from $\rm\ f(x^n) = f(x)^n\ $ for an (anti-) multiplicative map $\rm\:f\:.$

Slightly simpler and more general is to note that the map $\rm\ f(x) = b\:x\:b^{-1}\ $ is multiplicative, i.e. $\rm\:f(xy) = f(x)\:f(y)\:,\:$ so, by induction $\rm\ f(x^n) = f(x)^n\:.$

Similarly for the second problem $\rm\: f(x) = x^{-1}\: $ satisfies $\rm\ f(xy) = f(y)\:f(x)\:,\: $ therefore upon applying $\rm\ f\ \:$ to $\rm\ a^{-1}\! =\: x^n\ $ we infer that $\rm\ a\: =\: f(x^n) = f(x)^n = (x^{-1})^n\ \ $ (for $\rm\:n=3\:$ in your case).

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.